Carl R. Eklund (1909-1962) - Siple, Paul A. (ARCTIC, 1963)
Dr. Carl Robert Eklund, posthumous Fellow of the Arctic Institute of North America, prominent in arctic and antarctic research, Chief of the Polar and Arctic Branch of the U.S. Army Research Office, died on November 3, 1962 at the age of 53. His gregarious friendly nature, good humour and knack of story-telling made him a cherished friend of all who knew him. For 23 years he was a leading American specialist in ornithology and geographic research in both the north and south polar regions. His U.S. Government service in the Department of the Interior and the Department of the Army was approaching 29 years. Carl was born in Tomahawk, Wisconsin on January 27, 1909. . With solid training and experience he answered the lure of the polar regions. From 1939-41 he served as ornithologist at the East Base of the U.S. Antarctic Service. This was the first modern U.S. Government-sponsored expedition to Antarctica, and the third of Rear Admiral Richard E. Bird's Antarctic commands. In addition to his collection of animal life for the Department of the Interior, Fish and Wildlife Service, Carl made one of the longest antarctic dog sled journeys accompanying Finn Ronne in a landward encirclement of Alexander I Island from the Palmer Peninsula Station on Stonington Island. Islands sighted near the turning point of this journey were named the Eklund Islands in his honour by the Board of Geographical Names. From 1941 to 43 he returned to the U.S. Fish and Wildlife Service as research biologist in charge of game conservation and education on Indian reservations at Minneapolis, Minnesota. During World War II he served as commissioned officer, advancing to Major in the U.S. Army Air Force. He served in the Arctic Section of the Arctic Desert Tropic Information Center. . The call of the polar regions drew him south again. His skill and experience were needed by the IGY organizers of the National Academy of Sciences. He was appointed as the first Scientific Station Leader of the Wilkes Station, Antarctica. His field leadership was ...